Monoclonal Antibodies Capable of Inhibiting the Interaction of the Receptor Binding Domain of SARS-CoV-2 Virus with the Angiotensin-Converting Receptor 2 of Human Cells - T. A. Ivashchenko; Ya. O. Romanenko; A. S. Kartseva; M. V. Silkina; M. A. Mar’in; A. E. Khlyntseva; N. A. Zeninskaya; I. G. Shemyakin; V. V. Firstova (Проблемы особо опасных инфекций, 2024)
The aim of the work was to evaluate the ability of monoclonal antibodies to inhibit the interaction of the receptor binding domain (RBD) in S protein of SARS-CoV-2 virus variants, Wuhan-Hu-1 and BQ 1.1, with the angiotensin-converting receptor 2 (ACE2). Materials and methods. In this study, recombinant RBDs of Wuhan-Hu-1 and BQ 1.1 variants were used as antigens. For mouse monoclonal antibody (mMCA) production, hybridomas were cultured in vivo in BALB/c mice. mMCAs were isolated from ascitic fluid by ammonium sulfate treatment followed by purification through column affinity chromatography with Protein G Sepharose sorbent. The specific activity of mMCAs was assessed by immunoblot with recombinant RBD of Wuhan-Hu-1 variant. To identify the most promising mMCA, the neutralizing activity of mMCA was evaluated by enzyme-linked immunosorbent assay (ELISA) via immobilizing RBD on the surface of a microplate and using ACE2 in the form of horseradish peroxidase conjugate. Recombinant antigens were produced in ExpiCHO-S cell line (Gibco, USA). Results and discussion. Three mMCAs have been described as a result of the study: 5C3, 3F11, 1E6. All antibodies belong to immunoglobulins of subclass G and specifically interact with the RBD in S protein of SARS-CoV-2 virus. The most effective inhibition of the interaction between ACE2 and the RBD of BQ 1.1 strain was observed for murine MCA 3F11 (65 %), while the interaction with the RBD of Wuhan-Hu-1 strain was inhibited by mMCA 5C3 (91 %). The identified characteristics allow for considering the antibodies as potential candidates for the development of antibody-based therapeutics, thus expanding the possibilities of therapy for SARS-CoV-2 virus infection.